EDUCATIONAL ASSISTANCE FOR STUDENTS WITH SPECIAL EDUCATIONAL NEEDS IN SPAIN - Mattos, Maria Odete de [UNESP]; Bizelli, Jose Luis [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
The construction of the article is based on the contrast between document analysis and direct observation of educational services for students with special educational needs in Spain, a country that has been recognized as a reference in critical reflection and organization of care models for inclusive school. Starting from a brief presentation on the Spanish Educational System, work retrieves relevant aspects of the legal and institutional order that structures the inclusion in school, analyzing the human resources available to meet the specialized functions and aspects relating to school management, both as regards planning as to the practical operation of the service routines.
Keywords: Educational services; Special educational needs